Perspectives and Challenges of iOS Developers in Using Reactive Programming with RxSwift - Farias, Elaine Cruz; Zimmerle, Carlos; Gama, Kiev (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
Reactive programming, which deals with asynchronous data streams and events, is gaining popularity but remains underexplored as a research topic. In the iOS ecosystem, RxSwift stands out as a widely used framework for reactive programming despite its challenges. This study investigates the difficulties faced by iOS developers when using RxSwift. Semi-structured interviews were conducted, and a code comprehension questionnaire was applied to map developers’ perspectives and the main challenges encountered. The paradigm shift was identified as the primary obstacle, with specific difficulties in creating streams, managing memory, and handling concurrency. Architectural patterns and learning resources were also cited as significant barriers. This research provides an overview of reactive development with RxSwift in iOS, proposing ways to optimize the learning journey and maximize the benefits of this approach.